+0  
 
0
49
1
avatar

b^3 - 4b^2 - 21b = 0 

 Dec 10, 2018

Best Answer 

 #1
avatar+15350 
+2

b^3 - 4b^2 - 21b = 0       Factor out 'b'

b (b^2-4b-21) = 0          factor

b (b-7)(b+3)   = 0   

         for this to = 0     either ( b = 0)      or b-7 = 0    (b=7)     or b+3 = 0   (b=-3)

 Dec 10, 2018
 #1
avatar+15350 
+2
Best Answer

b^3 - 4b^2 - 21b = 0       Factor out 'b'

b (b^2-4b-21) = 0          factor

b (b-7)(b+3)   = 0   

         for this to = 0     either ( b = 0)      or b-7 = 0    (b=7)     or b+3 = 0   (b=-3)

ElectricPavlov Dec 10, 2018

25 Online Users

avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.